Effect of maturity stage at harvest on the ensilability of maize hybrids in the early and late FAO classes, grown in areas differing in yield potential. (22nd July 2019) - Marchesini, Giorgio; Serva, Lorenzo; Chinello, Maria; Gazziero, Matteo; Tenti, Sandro; Mirisola, Massimo; Garbin, Elisabetta; Contiero, Barbara; Grandis, Daniel; Andrighetto, Igino
Abstract: The aim of this study was to assess the effects of earliness (according to FAO class), maturity stage at harvest and environmental conditions on the ensilability of maize hybrids described by their fermentation products and by a fermentation quality index (FQI). Maize hybrids belonging to early ( n  = 14) and late ( n  = 15) FAO classes were grown in low, medium and high potential yield areas and harvested at an early (EH), medium (MH) and late maturity stage (LH), that is, at 1/3, 2/3 and 5 d after the 2/3 milk line stage, respectively, according to a split‐plot design. Upon harvest, each sample ( n  = 522) was analysed for dry matter (DM) and water‐soluble carbohydrates (WSC) before being ensiled in vacuum‐packed bags ( n  = 1, 044). After 60 days of conservation, samples were analysed for DM and fermentation products. In the pre‐ensiling phase, DM was higher in early hybrids ( p  = .001), low yield areas ( p  < .001) and at LH maturity ( p  < .001), whereas WSC contents were higher in early hybrids ( p  < .001), medium yield areas ( p  < .001) and at EH maturity ( p  < .001). With regard to silages, early hybrids had a higher FQI ( p  < .001), which was highest in areas with a high yield potential ( p  < .01) and at EH maturity ( p  < .01). Late hybrids proved to be better suited for low yield areas compared with early hybrids ( p  < .01) and had a higher FQI at EH and MH than at LH maturity ( p  < .01).